Review Valence, Review Volume and Product Return: The Mediation of Customer Expectation - Supriharyanti, Elisabeth -; -, Felicia -; Setyawan, Annisa Alfa (Inovbiz: Jurnal Inovasi Bisnis, 2023)
Customer reviews have transformed and created innovative ways for businesses to deliver their products. Their buying choices are often advised and guided by online reviews and it is a form of electronic word of mouth (eWOM) that today is an integral part of the online environment containing more information about a product or service experience. While shopping online, customers cannot physically see the product and it builds customer expectations which can lead to product returns. Therefore, this study will analyze the effect of review valence and review volume on product returns, using customer expectations as mediation. Data was collected through a survey of those who live in Indonesia and have considered returning products from the Erigo Online Store in several e-commerce sites. In addition, the relationship between each variable will be determined by using partial least squares-structural equation modeling (PLS-SEM). This research draws conclusions about the effect of online reviews on product returns. Thus, this research is expected to contribute to the field of consumer behavior.